A INSERÇÃO DO PROFESSOR NOS ANOS INICIAIS DO ENSINO FUNDAMENTAL: A CONSTRUÇÃO DE SUA IDENTIDADE PROFISSIONAL - Tânia Cristina Silva Pessoa; Raimunda Abou Gebran (Universidade do Oeste Paulista, 2016)
As in any profession, teacher training has a built trajectory historically marked by features that will be present in the construction of professional identity. The aim of this study was to analyze and identify the construction of teacher identity from the view of the beginning teacher in the Municipal Schools in elementary school in Rancharia/SP. The methodology used was qualitative research of descriptive and interpretative. A questionnaire and a semi structured interview with eight (8) beginners teachers of the Municipal Schools in Rancharia/SP was conducted for data collect . The preliminary results Indicated that the main problems of these professionals were: Difficulties in the development of the course contents, class management, correlation between theory and practice and a lack of experience and support from Managers and from Public Policy. It is concluded that it is extremely necessary to introduce support programs from the public sector to attend the inclusion of these professionals in the school environment.